Z doświadczeń uczestników projektu THRIECE – perspektywa dziecka i dorosłego - Agnieszka Nowak-Łojewska (Problemy Wczesnej Edukacji)
The text is a description of the international project THRIECE (Agreement 2017-1-IE01- KA201-025698) realised as Erasmus+ Programme in 2017-2020. Experiences of its participants (teachers and children 3 to 10 years old) were reconstructed. In this article a qualitative analysis of teachers’ utterances was applied and children’s narrations with mosaic approach were used. Classes observations, children’s utterances and their pieces of work were helpful. As a result of the research, an innovative approach was revealed with elements of holistic, relational and inclusive education, which are the three basic pillars of the project. These innovative ideas resulted in examples of new interesting educational practices.